Composite oxide particle and production method of oxysulfide particle

JP2025033504APending Publication Date: 2025-03-13SHINSHU UNIVERSITY +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023139261
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-08-29
Publication Date
2025-03-13

AI Technical Summary

Benefits of technology

【0016】 本発明の一態様によれば、粒径が小さい酸硫化物粒子を製造可能な新たな技術を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025033504000001
    Figure 2025033504000001
  • Figure 2025033504000002
    Figure 2025033504000002
  • Figure 2025033504000003
    Figure 2025033504000003
Patent Text Reader

Abstract

To provide a novel technology capable of producing oxysulfide particles with small particle diameters.SOLUTION: There is provided a composite oxide particle having a composition represented by a formula MaTibOc with a particle diameter D90 of less than 200 nm. Also provided is a method of producing an oxysulfide particle by combining sulfur with a complex oxide using the complex oxide particle as a precursor.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing composite oxide particles and oxysulfide particles. [Background technology]

[0002] In recent years, the development of high-performance photoenergy conversion systems that utilize solar energy as a renewable energy source has become increasingly important in order to curb global warming and to break away from dependency on dwindling fossil fuels. In particular, there is an increasing social demand for technology that uses solar energy to split water and produce hydrogen. The water splitting reaction in an acidic aqueous solution on photocatalyst particles is presumed to proceed as follows. H2O+2h + →1 / 2O2+2H + (1) 2H + +2e - →H2(2)

[0003] One known photocatalyst that causes such a reaction is Y2Ti2O5S2 (hereinafter also referred to as "YTOS"), which is generally synthesized through the following reaction (see, for example, Patent Document 1). Y2O3+6TiO2+2Y2S3→3Y2Ti2O5S2 [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2020-138188 A Summary of the Invention [Problem to be solved by the invention]

[0005] The photocatalytic action exhibited by oxysulfide particles such as YTOS usually has a crystal structure suitable for that action. In addition, from the viewpoint of increasing the activity of the photocatalyst, it is preferable that the particle size of the particulate photocatalyst is as small as possible, up to the wavelength of the irradiated light. As the development of the above-mentioned light energy conversion system becomes more important, there is a demand for a technology to manufacture oxysulfide particles with a small particle size.

[0006] An object of one aspect of the present invention is to provide a new technique capable of producing oxysulfide particles having a small particle size. [Means for solving the problem]

[0007] In order to solve the above problems, the present invention provides the following aspects.

[0008] [1] Particles of a composite oxide represented by the following formula, having a particle diameter of D 90 Composite oxide particles having a particle size of less than 200 nm. M a Ti b O c (In the formula, M is one or more elements selected from the group consisting of Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, and Y, and a:b:c=1.6-14.4:6:12-36.)

[0009] [2] The composite oxide particles according to [1], wherein in the formula, a:b:c=1.6-2.4:6:12-18.

[0010] [3] The composite oxide particles according to [1], wherein in the formula, a:b:c=4.8-7.2:6:16.8-25.2.

[0011] [4] The composite oxide particles according to [1], wherein in the formula, a:b:c=9.6-14.4:6:24-36.

[0012] [5] A method for producing oxysulfide particles, comprising a step of compounding the composite oxide particles according to any one of [1] to [4] with sulfur.

[0013] [6] The method for producing oxysulfide particles according to [5], wherein sulfur is compounded with the composite oxide by solid phase synthesis.

[0014] [7] The method for producing oxysulfide particles according to [5] or [6], wherein sulfur is compounded with the complex oxide by solid-phase synthesis using a flux.

[0015] [8] The method for producing oxysulfide particles according to [7], wherein an iodide is used as the flux. Effect of the Invention

[0016] According to one aspect of the present invention, a new technique capable of producing oxysulfide particles having a small particle size can be provided. [Brief description of the drawings]

[0017] [Figure 1] FIG. 1 is a diagram showing an electron microscope photograph of composite oxide particle 1 of Example 1. [Diagram 2] FIG. 2 is a diagram showing an electron microscope photograph of oxysulfide particles 1 of Example 2. [Diagram 3] FIG. 2 is a diagram showing an electron microscope photograph of oxysulfide particles 2 of Example 3. [Figure 4] FIG. 2 is a diagram showing an electron microscope photograph of oxysulfide particles C1 of Comparative Example 1. [Diagram 5] FIG. 2 is a graph showing the volume-based particle size distribution of composite oxide particles 1 of Example 1. [Figure 6] FIG. 2 is a graph showing the volume-based particle size distribution of oxysulfide particles 1 of Example 2. [Figure 7] FIG. 13 is a graph showing the volume-based particle size distribution of oxysulfide particles 2 in Example 3. [Figure 8] FIG. 2 is a graph showing the volume-based particle size distribution of oxysulfide particles C1 of Comparative Example 1. [Figure 9] FIG. 2 is a diagram showing X-ray diffraction charts of the composite oxide particles and oxysulfide particles of Examples 1 to 3 and Comparative Example 1. [Figure 10]FIG. 2 is a diagram showing the diffuse reflectance spectra of the oxysulfide particles of Examples 2 and 3 and Comparative Example 1. [Figure 11] FIG. 2 is a graph showing the photocatalytic properties of oxysulfide particles of Example 3 and Comparative Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0018] Hereinafter, one embodiment of the present invention will be described in detail. In the specification, the symbol "to" means a range including both the numerical values ​​at both ends.

[0019] [Composite oxide particles] The composite oxide particles referred to in the present invention refer to oxides containing two or more metal elements, and generally refer to those obtained by mixing and heating compounds containing multiple metal elements. These may be compounds, solid solutions, or mixtures, and any of these may be used. In the case of a mixture, it is preferable that at least one of the oxides containing different metal elements is nano-sized and fused to each other, rather than being a simple physical mixture.

[0020] The composite oxide particles according to one embodiment of the present invention are composite oxide particles represented by the following formula: M a Ti b O c In the formula, M is one or more elements selected from the group consisting of Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm and Y, and a:b:c=1.6-14.4:6:12-36.

[0021] M may be any element that exhibits photocatalytic function when combined with Ti and oxygen, or with sulfur (described later), by calcination or the like. M may be one or more elements. Among these, M is preferably Y, from the viewpoint of obtaining an oxysulfide MTOS having a small particle size and capable of responding to long wavelengths by using Y as a precursor in the production of the oxysulfide MTOS.

[0022] The complex oxide may have a plurality of compositions with different ratios of M to Ti. The complex oxide may have a composition with few defects in terms of stoichiometric composition and can be obtained stably. Examples of the complex oxide include a complex oxide with a ratio of M to Ti of about 1 / 3, a complex oxide with a ratio of M to Ti of approximately the same, or a complex oxide with a ratio of M to Ti of about twice. The complex oxide may be one of these, or a mixture of two or more of them.

[0023] In a composite oxide in which the ratio of M to Ti is about 1 / 3, a:b:c may be 1.6-2.4:6:12-18. Such a composite oxide is, for example, M2Ti6O 15 It can be expressed as:

[0024] In a composite oxide in which the ratio of M to Ti is approximately the same, a:b:c may be 4.8-7.2:6:16.8-25.2. Such a composite oxide is, for example, M6Ti6O 21 It can be expressed as:

[0025] In a composite oxide in which the ratio of M to Ti is about twice, a:b:c may be 9.6-14.4:6:24-36. Such a composite oxide is, for example, M12Ti6O 30 It can be expressed as:

[0026] The mixture of these composite oxides is also small particles, and M and Ti are mixed at the nano level, which is considered to be useful for producing small particles of sulfate oxide, which is the effect of the present invention.

[0027] In a composite oxide in which the ratio of M to Ti is about 1 / 3, the ratio of a to b=6 is preferably 1.4 or more, more preferably 1.6 or more, and even more preferably 1.8 or more, from the viewpoint of growing crystals of an oxysulfide with few impurities and defects when used as a precursor of an oxysulfide described below. In addition, the ratio of a to b=6 is preferably 15 or less, more preferably 14 or less, even more preferably 8 or less, and even more preferably 2.4 or less, from the viewpoint of growing crystals of an oxysulfide with few impurities and defects.

[0028] Furthermore, in a composite oxide in which the ratio of M to Ti is about 1 / 3, the ratio of c to b=6 is, from the viewpoint of growing oxysulfide crystals with few impurities and defects, preferably 10 or more, more preferably 11 or more, and even more preferably 12 or more. Moreover, from the viewpoint of growing oxysulfide crystals with few impurities and defects, c is preferably 36 or less, more preferably 32 or less, even more preferably 25 or less, and even more preferably 18 or less.

[0029] The composite oxide particles of one embodiment of the present invention may further contain other elements other than the above-mentioned M, titanium, and oxygen, within the range in which the effects of the present invention can be obtained. Examples of such other elements include alkali metal elements, alkaline earth metal elements, zinc (Zn), aluminum (Al), scandium (Sc), phosphorus (P), nitrogen (N), rare earth elements, and halogen elements. The other elements may be one or more, and are used in an amount that provides both the effects of the present invention and the effects of the other elements. Usually, the other elements are used in an amount (trace amount) on the order of ppm. The composite oxide particles of one embodiment of the present invention may not contain other elements other than M, titanium, and oxygen, except in the case of unavoidable contamination. An embodiment that does not substantially contain such other elements may also be a preferred embodiment of the present invention.

[0030] The composite oxide particles according to one embodiment of the present invention have a particle diameter of D 90It is less than 200 nm. 90 D means the value below which 90% of all composite oxide particles are located in the volume-based particle size distribution of the composite oxide particles. 90 For the purpose of improving the optical semiconductor performance of the resulting oxysulfide and from the viewpoint of controlling the particle size, D is preferably 190 nm or less, more preferably 180 nm or less, and even more preferably 160 nm or less. 90 From the viewpoints of ease of handling of the raw composite oxide during synthesis of the oxysulfide, efficiency of mixing with the sulfide, and control of the particle size of the produced oxysulfide, the particle size is preferably 10 nm or more, more preferably 20 nm or more, and even more preferably 30 nm or more.

[0031] [Manufacturing method] The composite oxide particles according to one embodiment of the present invention can be produced by a known technique for producing composite particles of two metal elements and oxygen. For example, the composite oxide particles according to one embodiment of the present invention can be produced by weighing, mixing, and firing a raw material of M and a raw material of Ti. The production method may further include other steps such as pulverization, washing, or surface treatment, as necessary.

[0032] <Raw materials> Examples of the raw material of M or the raw material of Ti include oxides, hydroxides, carbonates, nitrates, sulfates, oxalates, carboxylates, and halides of M or Ti. The raw materials of M and Ti can be appropriately selected from the above compounds depending on various conditions such as reactivity or the type and amount of gas generated during firing. Both the raw materials of M and Ti are preferably oxide particles from the viewpoint of suppressing gas generation during firing and from the viewpoint of being able to serve as a source of oxygen in the composite oxide.

[0033] When the raw material of M and the raw material of Ti are particles, the particle size is within the range of the above-mentioned D 90From the viewpoint of producing composite oxide particles having the above-mentioned D, it is preferable that the particle size of the raw material of M and the raw material of Ti is, in terms of the volume-based median diameter, preferably 1 nm or more, more preferably 2 nm or more, and even more preferably 3 nm or more, from the viewpoint of easy handling during production. 90 From the viewpoint of producing composite oxide particles having the above structure, the volume-based median diameter is preferably 140 nm or less, more preferably 120 nm or less, and even more preferably 110 nm or less.

[0034] The particle sizes of the M and Ti raw materials do not need to be the same. If the median size of the particle size of one of the raw materials exceeds 100 nm, the particle size of the other raw material should be adjusted to the D of the resulting composite oxide. 90 From the viewpoint of being in the above-mentioned preferred range, the volume-based median diameter is preferably 90 nm or less, more preferably 80 nm or less, and even more preferably 70 nm or less.

[0035] <Mixed> The method for mixing the raw material of M or the raw material of Ti may be a dry method or a wet method. A known mixing technique can be appropriately adopted for mixing the two raw materials.

[0036] Examples of mixing by the dry method include a method using a mixer such as a ribbon blender, a V-type blender, or a Henschel mixer, and mixing using a mortar and pestle. In such mixing, both raw materials may be ground before mixing using a dry grinding machine such as a hammer mill, a roll mill, a ball mill, or a jet mill.

[0037] Examples of mixing by the wet method include a method in which a solvent or dispersion medium is added to both raw materials and mixed using a grinder, a mortar and pestle, or an evaporating dish and a stirring rod to form a solution or slurry. Examples of the solvent or dispersion medium include water, methanol, and ethanol. In mixing by the wet method, the solution or slurry may be dried by a method such as spray drying, heat drying, or natural drying.

[0038] <Firing> The method of firing the raw material of M and the raw material of Ti is usually carried out by filling the mixture obtained by the above-mentioned mixing step into a heat-resistant container and firing it. The heat-resistant container is usually made of a material that has low reactivity with both raw materials. Examples of the heat-resistant container include a crucible and a tray. Examples of the material of the heat-resistant container include ceramics, metals, alloys containing them as main components, and carbon (graphite). Examples of ceramics include alumina, quartz, mullite, boron nitride, silicon carbide, silicon nitride, stabilized zirconia, titania, and magnesium oxide. Examples of metals include platinum, molybdenum, tungsten, tantalum, niobium, iridium, and rhodium.

[0039] If the temperature during firing (firing temperature) is too low, the crystals of the complex oxide may not grow sufficiently, resulting in a small particle size of the complex oxide particles. If the firing temperature is too high, the crystals may grow too much, resulting in a large particle size of the complex oxide particles. From the viewpoint of sufficient growth of the complex oxide crystals, the firing temperature is preferably 300°C or higher, more preferably 400°C or higher, and even more preferably 500°C or higher. Moreover, from the viewpoint of sufficiently reducing the particle size of the complex oxide particles, the firing temperature is preferably 900°C or lower, more preferably 850°C or lower, and even more preferably 800°C or lower.

[0040] The pressure during firing (firing pressure) can be appropriately determined with reference to other conditions such as the firing temperature. The firing pressure is usually 0.01 MPa or more, preferably 0.1 MPa or more, and usually 200 MPa or less, preferably 100 MPa or less. From the viewpoint of industrial production such as cost and labor, the firing pressure is preferably from atmospheric pressure to about 1 MPa.

[0041] The calcination time can be appropriately determined with reference to other conditions such as the calcination temperature and the calcination pressure. If the calcination time is too short, the crystal growth of the composite oxide may be insufficient, and if it is too long, it is disadvantageous from the viewpoint of productivity. The calcination time is usually 10 minutes or more, preferably 1 hour or more, more preferably 3 hours or more, and even more preferably 4 hours or more. In addition, the calcination time is usually 24 hours or less, preferably 15 hours or less.

[0042] The atmosphere during firing may be air or a gas other than oxygen. The gas other than oxygen may be one or more kinds, examples of which include carbon monoxide, carbon dioxide, nitrogen, hydrogen and argon. From the viewpoint of convenience, it is preferable that the atmosphere during firing is air.

[0043] As mentioned above, the composite oxide particles in the present invention refer to oxides containing two or more metal elements, and generally refer to those obtained by mixing and heating compounds containing multiple metal elements, and may be any of compounds, solid solutions, and mixtures. However, in the case of a mixture, it is preferable that at least one of the oxides containing different metal elements is nano-sized and fused to each other, so that the different metal elements are mixed at the nano level and are dispersed and arranged with each other, rather than simply being a physical mixture. Such fused composite oxides can be synthesized by the synthesis method already described. In addition, whether or not the mixture is a mixture can be determined by XRD, SEM-EDS, Rietveld analysis of XRD, etc.

[0044] The above elements and their ratios in the composite oxide particles according to one embodiment of the present invention can be measured by X-ray diffraction (XRD), ICP (inductively coupled plasma) analysis, or XRF (X-ray fluorescence analysis). The elements and their ratios can be adjusted by the types and amounts of the oxide particles used as raw materials.

[0045] In addition, D of the composite oxide particles according to one embodiment of the present invention 90 can be determined by a known particle size distribution measurement technique that utilizes a laser diffraction / scattering method. 90 It can be adjusted by the particle size of the raw material of the composite oxide and the calcination temperature, or by classification or mixing of classified products.

[0046] In addition, in the composite oxide particles according to one embodiment of the present invention, it is possible to measure by SEM-EDS whether the oxides containing different metal elements are fused to each other. Furthermore, it is possible to measure by D 90 One guideline is that the thickness should be less than 200 nm.

[0047] [Application] The composite oxide particles according to one embodiment of the present invention have a small particle size and are useful as a raw material (precursor) for oxysulfide particles which are useful as photocatalysts for artificial photosynthesis.

[0048] [Method for producing oxysulfide particles] A method for producing oxysulfide particles (hereinafter also referred to as "oxysulfide particles") in one embodiment of the present invention includes a step of compounding sulfur with the composite oxide of the composite oxide particles in one embodiment of the present invention described above.

[0049] [Oxysulfide particles] The composition of the oxysulfide of one embodiment of the present invention can be represented by the following formula. M d Ti e O f S g In the formula, M is the same as M in the formula of the composite oxide according to one embodiment of the present invention described above. Furthermore, in the formula, d:e:f:g=1.7-2.3:2:4.7-5.3:1.7-2.3.

[0050] From the viewpoints of maintaining the crystal structure or reducing crystal defects, and suppressing impurities, d is preferably 1.7 or more, more preferably 1.8 or more, and even more preferably 1.85 or more, when the number of moles of Ti, e, is 2. Also, from the viewpoints of maintaining the crystal structure or reducing crystal defects, d is preferably 2.3 or less, more preferably 2.2 or less, and even more preferably 2.15 or less, when the number of moles of Ti, e, is 2.

[0051] When the number of moles e of Ti is 2, f is preferably 4.7 or more from the viewpoint of maintaining the crystal structure or reducing crystal defects, suppressing impurities, and the stability of the photocatalyst in water, more preferably 4.8 or more, and even more preferably 4.85 or more. When the number of moles e of Ti is 2, f is preferably 5.3 or less from the viewpoint of maintaining the crystal structure or reducing crystal defects, and preventing the band gap of the photocatalyst particles from widening, more preferably 5.2 or less, and even more preferably 5.15 or less. If f is out of the above range, the crystal structure of MTOS may not be maintained. Also, if f is too small, the stability of the material in water may decrease, and if f is too large, the band gap may widen and it may not be possible to absorb long-wavelength light.

[0052] When the number of moles e of Ti is 2, g is preferably 1.7 or more from the viewpoint of maintaining the crystal structure or reducing crystal defects, suppressing impurities, and preventing the band gap of the photocatalyst particles from widening, more preferably 1.8 or more, and even more preferably 1.85 or more. When the number of moles e of Ti is 2, g is preferably 2.3 or less from the viewpoint of maintaining the crystal structure or reducing crystal defects, suppressing impurities, maintaining the stability of the photocatalyst in water, and maintaining the surface hydrophilicity, more preferably 2.2 or less, and even more preferably 2.15 or less. If g is out of the above range, the crystal structure of MTOS may not be maintained. If g is too small, the band gap may widen, making it impossible to absorb long-wavelength light, and if g is too large, the stability of the material in water may decrease, and the surface may become hydrophobic, which may be disadvantageous to the water splitting reaction.

[0053] [Sulfur compounding process] The step of compounding sulfur may be a gas-phase synthesis in which the sulfur of a gaseous sulfur raw material is compounded with the composite oxide of the composite oxide particles, or a solid-phase synthesis in which the sulfur of a solid sulfur raw material is compounded with the composite oxide of the composite oxide particles. According to one aspect of the present invention, it is possible to produce oxysulfide particles having a smaller particle size than when the raw materials of the composite oxide particles (the material of M and the material of Ti) are directly compounded with the sulfur of the sulfur material.

[0054] The sulfur raw material can be appropriately selected within a range that can be combined with the composite oxide depending on the conditions of the step of combining sulfur. The sulfur raw material may be one or more kinds. In the case of gas-phase synthesis, examples of the sulfur raw material include S, H2S (hydrogen sulfide), CS2 (carbon disulfide) and COS (carbonyl sulfide). In the case of solid-phase synthesis, examples of the sulfur raw material include S, M2S3, M2O2S and TiS2.

[0055] The step of compounding sulfur may be gas phase synthesis or solid phase synthesis, but from the viewpoint of not using toxic gases in the production process, the step of compounding sulfur is preferably solid phase synthesis.

[0056] In the production of oxysulfide particles according to one embodiment of the present invention, impurities such as oxide phases may be generated in the oxysulfide particles due to the inclusion of air or moisture in the system. Therefore, the production method of oxysulfide particles according to one embodiment of the present invention is preferably carried out in a closed environment such as a glove box with a dew point of −20° C. or lower under an inert gas atmosphere such as nitrogen, in order to prevent the inclusion of air or a trace amount of moisture.

[0057] In the solid-phase synthesis, it is preferable to combine sulfur with the composite oxide by solid-phase synthesis using a flux from the viewpoint of reducing the diameter of the oxysulfide particles produced and from the viewpoint of shortening the calcination time for combining sulfur, which will be described later.

[0058] The flux component may be, for example, an alkali metal or alkaline earth metal halide. The flux component may be one or more types. The flux component may be appropriately selected from the viewpoints of handling, state under firing conditions, effect as a flux component, or ease of removal after firing, depending on the firing conditions in the step of compounding sulfur. Examples of the flux component include chlorides of Li, Na, K, Rb, Cs, Mg, Ca, Sr, and Ba, bromides of these metals, and iodides of these metals.

[0059] Among them, the iodide flux component can be easily removed by washing the reaction product after firing with hot water. Therefore, from the viewpoint of ease of removal after firing, it is preferable to use iodide as a flux component. In addition, iodide is less corrosive than chloride, and iodide ions have less impact on surrounding materials (e.g., electronic devices, other photocatalytic materials, module substrates, etc.) when remaining in the product compared to chloride ions. Therefore, it is preferable to use iodide from the viewpoint of manufacturing equipment maintenance and the impact on the surroundings when remaining.

[0060] The mixing ratio of the flux components to the composite oxide particles and sulfur raw material (hereinafter also referred to as "oxysulfide particle raw material") is preferably 0.01 times or more, more preferably 0.1 times or more, and even more preferably 0.5 times or more, by mass, relative to the oxysulfide particle raw material, from the viewpoint of sufficiently proceeding with the composite reaction of sulfur. Moreover, the mixing ratio of the flux components to the oxysulfide particle raw material is preferably 50 times or less, more preferably 40 times or less, and even more preferably 30 times or less, by mass, relative to the oxysulfide particle raw material, from the viewpoint of improving the yield of oxysulfides by increasing the amount of the oxysulfide particle raw material charged.

[0061] In the step of compounding sulfur, the oxysulfide particle raw material is fired, if necessary, in the presence of a flux component.

[0062] The firing temperature in the step of compounding sulfur is preferably 500° C. or higher, more preferably 550° C. or higher, and even more preferably 600° C. or higher, from the viewpoint of sufficiently proceeding with the compounding reaction (by sufficiently melting the flux component in the case of blending a flux component). Moreover, the firing temperature is preferably 1000° C. or lower, more preferably 950° C. or lower, and even more preferably 900° C. or lower, from the viewpoint of suppressing the generation of an oxide impurity phase and preventing the coarsening of oxysulfide particles.

[0063] In addition, in the calcination, the temperature may be increased to the desired calcination temperature at a constant rate, or the rate of temperature increase may be appropriately changed to increase the temperature to the desired calcination temperature stepwise at two or more rates of temperature increase. The optimal method for increasing the temperature varies depending on the properties of the compound, so any optimal method may be used from the viewpoint of crystallinity or particle size control of the product.

[0064] The calcination time in the step of compounding sulfur is preferably 0.05 hours or more, more preferably 0.5 hours or more, from the viewpoint of suppressing the generation of an impurity phase, and is preferably 500 hours or less, more preferably 300 hours or less, from the viewpoint of preventing coarsening of oxysulfide particles.

[0065] The firing atmosphere in the step of compounding sulfur is preferably in a vacuum in terms of preventing side reactions. Firing in such a vacuum atmosphere can be performed, for example, by sealing the oxysulfide particle raw material (and the flux component, if necessary) in a glass tube in a vacuum atmosphere and placing the glass tube in a firing temperature environment.

[0066] [Other processes] The method for producing oxysulfide particles according to one embodiment of the present invention may further include other steps than the step of compounding sulfur described above, within the scope of the effects of the present invention. For example, after firing, in order to remove excess sulfur from the particles produced by oxidation treatment, the particles may be subjected to a heat treatment in which the particles are heated in air at a temperature of 100 to 300°C for about 0.1 to 3 hours. In addition, when a flux component is used in the step of compounding sulfur, the particles subjected to the heat treatment may be washed to remove the flux component.

[0067] [Uses of oxysulfide particles] The oxysulfide particles according to one embodiment of the present invention are effective as photocatalysts for water splitting and exhibit particularly high photocatalytic activity. The photocatalyst can perform total water splitting using a single electrode, i.e., without the need for a counter electrode.

[0068] The oxysulfide particles according to one embodiment of the present invention are capable of generating hydrogen and oxygen without using a sacrificial reagent. The oxysulfide particles according to one embodiment of the present invention are also capable of generating hydrogen and oxygen on the same electrode. Note that the "electrode" in photocatalysis refers to a laminate in which a photocatalyst layer containing the oxysulfide particles according to one embodiment of the present invention is provided on a substrate.

[0069] The oxysulfide particles according to one embodiment of the present invention can be suspended in a cocatalyst-containing solution and subjected to MW (microwave) treatment to prepare a photocatalyst for evaluation in a short time. For the MW treatment, for example, Anton Paar's "Microwave synthesis Reactor Monowave 300" or the like can be used, and the recommended conditions can be appropriately selected to perform the treatment.

[0070] The oxysulfide particles according to one embodiment of the present invention exhibit sufficient photocatalytic activity by themselves, but are preferably used together with a promoter.

[0071] The co-catalysts include an oxidation reaction co-catalyst (oxygen generation side) and a reduction reaction co-catalyst (hydrogen generation side), and it is preferable that one or both of these are supported on the oxysulfide particles of one embodiment of the present invention.

[0072] Examples of the oxidation reaction promoter include metals in Groups 2 to 14 of the periodic table, intermetallic compounds of the metals, alloys of the metals, and compounds thereof. An "intermetallic compound" is a compound formed from two or more metal elements. The atomic ratio of components constituting an intermetallic compound does not necessarily have to be a stoichiometric ratio, and may be in a composition range wider than the stoichiometric ratio. Examples of the "compound" in "these compounds" include oxides, composite oxides, nitrides, oxynitrides, sulfides, oxysulfides, and mixtures thereof.

[0073] The oxidation reaction promoter is preferably a metal, an oxide of the metal, or a composite oxide of the metal, such as Mg, Ti, Mn, Fe, Co, Ni, Cu, Ga, Ru, Rh, Pd, Ag, Cd, In, Ce, Ta, W, Ir, Pt, or Pb. More preferably, the oxidation reaction promoter is a metal, an oxide of the metal, or a composite oxide of the metal, such as Mn, Co, Ni, Ru, Rh, or Ir. Even more preferably, the oxidation reaction promoter is Ir, MnO, MnO2, Mn2O3, Mn3O4, CoO, Co3O4, NiCo2O4, RuO2, Rh2O3, or IrO2.

[0074] Examples of the reduction reaction promoter include metals of Groups 3 to 13 of the periodic table, intermetallic compounds of the metals, alloys of the metals, and compounds thereof. The intermetallic compounds are the same as those described above. Examples of the "compounds" of "these compounds" include oxides, composite oxides, oxynitrides, sulfides, oxysulfides, carbides, nitrides, and mixtures thereof. The reduction reaction promoter is preferably Pt, Pd, Rh, Ru, Ni, Au, Fe, NiO, RuO2, IrO2, Rh2O3, and Cr-Rh composite oxides, core-shell type Rh / Cr2O3, or Pt / Cr2O3.

[0075] The amount of the co-catalyst metal supported on the oxysulfide particles may be appropriately determined within a range in which the desired photocatalytic function is expressed. From the viewpoint of fully expressing the photocatalytic function, the amount of the oxidation reaction co-catalyst metal supported on the oxysulfide particles is preferably 0.01 parts by mass or more, and more preferably 0.05 parts by mass or more, relative to 100 parts by mass of the oxysulfide particles. In addition, from the viewpoint of achieving both the expression of the photocatalytic function and the reduction in the amount of the co-catalyst used, the amount of the co-catalyst metal supported on the oxysulfide particles is preferably 5 parts by mass or less, more preferably 4 parts by mass or less, and even more preferably 3 parts by mass or less, relative to 100 parts by mass of the oxysulfide particles.

[0076] From the same viewpoint as the metal loading amount of the oxidation reaction promoter, the metal loading amount of the reduction reaction promoter on the oxysulfide particles is preferably 0.01 parts by mass or more per 100 parts by mass of the oxysulfide particles. The metal loading amount of the reduction reaction promoter on the oxysulfide particles is preferably 20 parts by mass or less, more preferably 15 parts by mass or less, and even more preferably 10 parts by mass or less. The "metal loading amount" refers to the amount of metal element in the promoter supported on the oxysulfide particles.

[0077] The form in which the oxysulfide particles or the oxysulfide particles carrying the above-mentioned co-catalyst in one embodiment of the present invention (hereinafter, these are also collectively referred to as "photocatalyst particles") are actually used for water splitting may be any form suitable for use in water splitting. Examples of such forms include a form in which the photocatalyst particles are dispersed in water, a form in which the photocatalyst particles are solidified to form a molded body and the molded body is placed in water, a form in which a photocatalyst layer is provided on a substrate to form a laminate and the laminate is placed in water, and a form in which the photocatalyst particles are fixed on a current collector to form an electrode for a water splitting reaction using a photocatalyst and the counter electrode are placed in water.

[0078] In particular, when the photochemical water-splitting reaction is carried out on a large scale, the electrode may be used as a photochemical water-splitting reaction electrode from the viewpoint of promoting the water-splitting reaction by applying a bias. In another embodiment, a laminate having a photocatalytic layer containing oxysulfide particles on a substrate, or a composite containing oxysulfide particles, may be placed in water without applying a bias. This embodiment is preferable from the viewpoints of ease of processing and handling, ease of maintenance, and cost reduction when used as an artificial photosynthesis device using a large area. Therefore, this embodiment is even more effective from the viewpoint of obtaining an industrially advantageous water splitting device, oxygen generating device, hydrogen generating device, or artificial photosynthesis system.

[0079] The electrode for photochemical water splitting reaction can be produced by a known method. For example, it can be easily produced by the so-called particle transfer method (Chem. Sci., 2013, 4, 1120-1124). In the particle transfer method, the electrode for photochemical water splitting reaction is generally produced by the following procedure. That is, the oxysulfide particles according to one embodiment of the present invention are placed on a first substrate such as glass to obtain a laminate of a photocatalyst layer and a first substrate layer. A conductive layer (current collector) is provided on the surface of the photocatalyst layer of the obtained laminate by deposition or the like. Here, the oxysulfide particles on the conductive layer side surface layer of the photocatalyst layer are fixed to the conductive layer. Thereafter, a second substrate is adhered to the surface of the conductive layer, and the conductive layer and the photocatalyst layer are peeled off from the first substrate layer. Since a part of the oxysulfide particles is fixed to the surface of the conductive layer, it is peeled off together with the conductive layer, and as a result, an electrode for photochemical water splitting reaction having a photocatalyst layer, a conductive layer, and a second substrate layer can be obtained.

[0080] Alternatively, as another method, a slurry in which the oxysulfide particles according to one embodiment of the present invention are dispersed may be applied to the surface of a current collector and dried to obtain an electrode for a water-splitting reaction. Alternatively, the oxysulfide particles and a current collector may be integrated by pressure molding or the like to obtain an electrode for a water-splitting reaction. Alternatively, a current collector may be immersed in a slurry in which the oxysulfide particles are dispersed, and a voltage may be applied to cause the oxysulfide particles to accumulate on the current collector by electrophoresis.

[0081] Alternatively, the co-catalyst may be supported in a later step. For example, in the above-mentioned particle transfer method, after obtaining a laminate having a photo-semiconductor layer, a conductive layer, and a second base layer, oxide particles as a co-catalyst may be supported on the surface of the photo-semiconductor layer to obtain an electrode for a water-splitting reaction.

[0082] In one embodiment of the present invention, the photocatalyst particles or the electrode for the water-splitting reaction described above are immersed in water or an aqueous electrolyte solution, and the photocatalyst particles or the electrode for the water-splitting reaction are irradiated with light to perform water splitting, thereby producing either hydrogen or oxygen, or both.

[0083] For example, as described above, photocatalyst particles are fixed on a current collector made of a conductor to obtain an electrode for a photochemical water splitting reaction, while a conductor carrying a hydrogen generation catalyst is used as a counter electrode, and light is applied while liquid or gaseous water is supplied to promote the water splitting reaction. If necessary, a potential difference can be provided between the electrodes to promote the water splitting reaction. Alternatively, an optical semiconductor carrying a hydrogen generation catalyst may be used as the counter electrode. In this case, a known optical semiconductor that catalyzes the hydrogen generation reaction can be used as the optical semiconductor.

[0084] Alternatively, the water splitting reaction may be promoted by irradiating light to an immobilized material in which photocatalyst particles are immobilized on an insulating substrate, or to a molded body formed by pressure molding of photocatalyst particles, while supplying water. Alternatively, the photocatalyst particles may be dispersed in water or an aqueous electrolyte solution, and the dispersion may be irradiated with light to promote the water splitting reaction. In this case, the water splitting reaction can be promoted by stirring as necessary.

[0085] The photocatalyst particles in one embodiment of the present invention can produce hydrogen and oxygen by placing the photocatalyst particles in water, supplying water thereto, and extracting one or both of hydrogen and oxygen. The generated hydrogen and oxygen can be separated using a gas separation member such as a zeolite membrane.

[0086] The reaction conditions for producing hydrogen and oxygen can be appropriately set within the range in which hydrogen and oxygen can be produced. For example, the reaction temperature may be 0° C. or higher and 200° C. or lower, and the reaction pressure may be 2 MPa (G) or lower.

[0087] The light irradiated during the production of hydrogen and oxygen may be visible light having a wavelength of 650 nm or less, or ultraviolet light. The light irradiated may be natural light or light from a light source. Examples of the light source include lamps capable of irradiating light similar to sunlight, such as xenon lamps or metal halide lamps, mercury lamps, and LEDs.

[0088] 〔summary〕 In one embodiment of the present invention, oxysulfide particles are produced using a composite oxide as a precursor. For example, when M is yttrium (Y), in one embodiment of the present invention, a composite oxide of Y2O3-TiO2 is first synthesized using oxide nanoparticles as a raw material, and the resulting composite oxide is used as a precursor to produce oxysulfide particles. As a result, oxysulfide particles having a smaller particle size are obtained compared to known synthesis methods. xY2O3+yTiO2→YTO(nanoparticles) YTO+zY2S3→Y2Ti2O5S2 (x=1 / 3, y=2, z=2 / 3)

[0089] As described above, according to the present invention, it is possible to efficiently produce a photocatalyst with higher performance for artificial photosynthesis. Therefore, according to the present invention, it is expected to contribute to the achievement of, for example, Goal 7 of the Sustainable Development Goals (SDGs) proposed by the United Nations, "Affordable and Clean Energy."

[0090] The present invention is not limited to the above-described embodiments, and various modifications are possible within the scope of the claims. An embodiment obtained by appropriately combining the technical means disclosed in each of the different embodiments is also included in the technical scope of the present invention. EXAMPLES

[0091] An embodiment of the present invention will be described below. First, measurements in the following embodiment and comparative example will be described.

[0092] (1) Particle size The volumetric particle size (D 50 Or D 90 ) was evaluated by the laser diffraction / scattering method. A nanoparticle size distribution analyzer "SALD-7100" (Shimadzu Corporation) was used as the measuring device, and about 10 mg of the sample was placed in the sampler tank. After ultrasonic treatment was performed as necessary using water (no dispersant) as the dispersion medium, the suspension was irradiated with a single 375 nm ultraviolet semiconductor laser beam. The ultrasonic treatment time and measurement interval were appropriately adjusted, and a graph of the average particle size distribution was extracted from multiple measurements, and the particle size was calculated from the graph.

[0093] (2) Compound composition The compositions of the components in the composite oxide particles and oxysulfide particles were identified by powder X-ray diffraction. A multipurpose X-ray diffractometer "SmartLab" (registered trademark, manufactured by Rigaku Corporation) was used as the measuring device, and measurements were performed under the following conditions.

[0094] X-ray: 40 Cu Kα Measurement angle: 2θ=5-80° Sampling width: 0.02° Scan speed: 10°min -1 Voltage: 30kV Current: 40mA

[0095] (3) Particle shape The shapes of the composite oxide particles and oxysulfide particles were measured and observed using a field emission scanning electron microscope "JSM-7600F" or a scanning electron microscope "JCM-5700" (both manufactured by JEOL Ltd.) at an accelerating voltage of 5-15 kV.

[0096] (4) Diffuse reflectance spectrum The diffuse reflectance spectrum of the oxysulfide particles was measured using an ultraviolet-visible (UV-vis) spectrophotometer "V670" (manufactured by JASCO Corporation). Measurement conditions; Measurement range: 250nm~850nm Data interval: 0.5nm Scanning speed: 100nm / min Light source switching: 340.0 nm Data analysis software: Spectra Manager version 2 Analysis: Kubelka-Munk (KM) transformation of the vertical axis Kubelka-Munk transformation formula: f(R ∞ )=(1-R ∞ ) 2 / 2R ∞ =K / S Here, f(R ∞ ) is the KM function, R ∞ is the absolute reflectance, K is the molar extinction coefficient, and S is the scattering coefficient.

[0097] The absolute reflectance of the sample R ∞ It is difficult to measure the relative reflectance r ∞ Therefore, the following formula is generally used. r ∞ = r(measurement sample) / r(standard sample) (BaSO4 is used as the standard sample) Using the relative reflectance r ∞ The measurement was performed according to the following formula: f(r ∞ )=(1-r ∞ ) 2 / 2r ∞ =K / S Derived from.

[0098] (5) Photocatalytic properties <Preparation of photocatalyst IrO2 / Y2Ti2O5S2 for oxygen generation evaluation> The oxysulfide particles and iridium chloride hydrate were dispersed in distilled water and heated at 150°C for 10 minutes using a microwave synthesis apparatus "Monowave 200" (manufactured by Anton Paar) to prepare a sample carrying 0.5 mass% Ir as a promoter.

[0099] <Oxygen generation evaluation test> The prepared photocatalyst for evaluating oxygen generation was used to evaluate the photochemical water-splitting reaction performance. The photochemical water-splitting reaction was carried out in a closed reaction apparatus equipped with a vacuum exhaust pump, a circulation pump, a cell for holding the photocatalyst immobilized material, a gas sampling valve, and a gas chromatograph (GC). A 300 W xenon lamp (λ>420 nm) was used as the light source, and the cell was cooled from the outside using cooling water. Before the evaluation, the reaction apparatus was evacuated several times to confirm that no air remained. The degree of vacuum was 4×10 4 The pressure was set to about Pa. After that, light irradiation was started and the amount of gas produced was measured. Analysis was performed using a gas chromatograph "GC-2014" (Shimadzu Corporation) with a column (molecular sieve 5A), carrier gas (argon) and temperature (50°C). The test was performed by sealing 150 mL of 0.02 M AgNO3 aqueous solution containing La2O3 (0.20 g) as a pH buffer for 200 mg of photocatalyst in a cell.

[0100] Example 1 The following components were wet mixed with ethanol in the amounts shown below for 10 minutes. The particle size of the Y2O3 particles was <10 nm in volume median diameter. The TiO2 particles were Wako Grade 1 manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., and had a particle size of 80 nm in volume median diameter. Yttrium oxide (Y2O3) particles 5.13g, Titanium dioxide (TiO2) particles 2.40g

[0101] Next, about 7 g of the resulting mixture was heated in air at 300°C for -1 The temperature was raised to 550°C under the above conditions, and the mixture was sintered at 550°C for 10 hours. 15 The composite oxide particles 1 represented by the formula: 90 was 85 nm on a volume basis.

[0102] Example 2 The following components were mixed in the following amounts in a glove box: Y2S3 particles were manufactured by Kojundo Chemical Laboratory Co., Ltd., and the particle size was 2.6 nm in volume median diameter. Composite oxide particles 1 0.71g Yttrium sulfide (Y2S3) particles 0.55g

[0103] Next, the obtained mixed particle 1 was further dry-mixed with the following components in the amounts shown below for 10 minutes to obtain raw material powder 1. Sulfur (S) was Wako Grade 1 manufactured by Fujifilm Wako Pure Chemical Industries, Ltd. Sulfur (S) 0.07g

[0104] Next, raw powder 1 is placed in a glass tube, vacuum sealed, and heated in an electric furnace until it reaches 500°C for 300°C·h. -1 Then, the temperature was increased to 800°C for 60°C·h. -1 The temperature was raised under the above conditions and the specimen was held at 800°C for 96 hours.

[0105] Next, the glass tube was broken in air to take out the produced powder, thus obtaining oxysulfide particles 1 represented by Y2Ti2O5S2.

[0106] Example 3 The following ingredients were mixed in the amounts listed below in a glove box: Composite oxide particles 1 0.356g Y2S3 particles 0.28g

[0107] Next, the obtained mixed particles 2 were further dry-mixed with the following components in the amounts shown below for 10 minutes to obtain raw material powder 2. S 0.04g Cesium iodide (CsI) 3.51g

[0108] Next, the raw material powder 2 is placed in a glass tube, vacuum sealed, and heated in an electric furnace until it reaches 500°C for 300°C·h. -1 Then, the temperature was increased to 700°C for 60°C·h. -1 The temperature was raised under the above conditions and then held at 700°C for 17 hours.

[0109] The glass tube was then broken in air to take out the powder. The powder was then fired at 200°C for 1 hour and washed with hot water to remove the flux component (CsI). Thus, oxysulfide particles 2 represented by Y2Ti2O5S2 were obtained.

[0110] Comparative Example 1 The following ingredients were dry mixed in the amounts shown below for 10 minutes to homogenize. Y2O3 particles 0.238g Y2S3 particles 0.58g TiO2 particles 0.503g S 0.15g 0.82g CsI

[0111] The obtained raw powder C1 was placed in a glass tube, vacuum sealed, and heated in an electric furnace up to 500°C for 300°C·h. -1 The temperature was raised to 700°C under the conditions of 60°C·h -1 The temperature was raised under the above conditions and then held at 700°C for 17 hours.

[0112] The glass tube was then broken in air to take out the powder. The powder was then fired at 200°C for 1 hour and washed with hot water to remove the flux component (CsI). Thus, oxysulfide particles C1 represented by Y2Ti2O5S2 were obtained.

[0113] 〔evaluation〕 1 to 4 show electron microscope photographs of the composite oxide particles and oxysulfide particles of Examples 1 to 3 and Comparative Example 1, respectively, and FIGS. 5 to 8 show the volume-based particle size distributions of the composite oxide particles and oxysulfide particles of Examples 1 to 3 and Comparative Example 1, respectively.

[0114] The composite oxide particle 1 of Example 1 is composed of particles of approximately nano-order size as shown in FIG. 1 and FIG. 5. 90 is approximately 0.1 μm.

[0115] The oxysulfide particles 1 and 2 in Examples 2 and 3 were both produced using the composite oxide particles 1 as a raw material. Therefore, the oxysulfide particles 1 in Example 2 were composed of particles having a size on the order of approximately microns, as shown in Figs. 2 and 6, and their D 90 The D is about 20 μm. As shown in FIG. 3 and FIG. 7, the oxysulfide particles 2 of Example 3 are manufactured using a flux, and therefore are composed of particles smaller than the oxysulfide particles 1. The oxysulfide particles 2 of Example 3 are composed of particles of approximately micron order size, and the D 90 is approximately 10 μm.

[0116] In contrast, the oxysulfide particles C1 of Comparative Example 1 were produced using flux, but coarse particles and fine particles were mixed, as shown in Figs. 4 and 8. 90 is approximately 20 μm.

[0117] From the above, it is understood that by producing oxysulfide particles by sulfurizing fine composite oxide particles, it is possible to produce oxysulfide particles having a relatively narrow particle size distribution and a small particle size.

[0118] 9 shows X-ray diffraction charts of the composite oxide particles and oxysulfide particles of Examples 1 to 3 and Comparative Example 1. Comparing the composite oxide particle 1 of Example 1 with the reference TiO2 (middle part of FIG. 9) and Y2O3 charts, it is characterized by having both TiO2 and Y2O3 peaks. Comparing the oxysulfide particle 1 of Example 2 and the oxysulfide particle 2 of Example 3 with the reference Sm2Ti2O5S2 and TiO2 charts (bottom part of FIG. 9), it can be confirmed that the desired oxysulfide structure is produced although it contains TiO2 as a by-product, and both have relatively smooth baselines and the relative magnitude relationships between peaks in the same chart are similar.

[0119] In contrast, the oxysulfide particles C1 of Comparative Example 1 have a relatively disturbed baseline, and the relative magnitude relationship between peaks in the same chart may be different when compared with Examples 2 and 3. This indicates that the oxysulfide particles C1 of Comparative Example 1 are more likely to undergo crystal growth in a specific crystal plane direction than the oxysulfide particles 1 of Example 2 and the oxysulfide particles 2 of Example 3.

[0120] 10 shows the diffuse reflectance spectra of the oxysulfide particles of Examples 2 and 3 and Comparative Example 1. The oxysulfide particles 1, 2 and C1 all have peaks around 400 to 500 nm. Compared with the oxysulfide particle C1 of Comparative Example 1, the oxysulfide particles 1 and 2 of Examples 2 and 3 have higher intensity around 400 to 500 nm and lower intensity at 650 to 800 nm. Thus, compared with the oxysulfide particle C1 of Comparative Example 1, the oxysulfide particles 1 and 2 of Examples 2 and 3 have higher absorption characteristics for light in the range of 400 to 500 nm and smaller background absorption in the range of 650 to 800 nm.

[0121] 11 shows the photocatalytic properties of the oxysulfide particles of Example 3 and Comparative Example 1. The oxysulfide particles 2 of Example 3 exhibit a high ability to generate oxygen immediately after the start of light irradiation, compared to the oxysulfide particles C1 of Comparative Example 1. This is believed to be because the oxysulfide particles 2 have a smaller particle size and a larger specific surface area than the oxysulfide particles C1, and because the oxysulfide particles C1 grow in a specific crystal plane direction, resulting in a lower ratio of crystal planes advantageous for oxygen generation. [Industrial Applicability]

[0122] The present invention can be used to develop higher performance photocatalysts for artificial photosynthesis.

Claims

1. Particles of a composite oxide represented by the following formula, having a particle diameter of D 90 The composite oxide particles have a particle size of less than 200 nm. M a Till b Oh c (In the formula, M is one or more elements selected from the group consisting of Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, and Y, and a:b:c=1.614.4:6:12-36.)

2. 2. The composite oxide particles according to claim 1, wherein in the formula, a:b:c=1.6-2.4:6:12-18.

3. 2. The composite oxide particles according to claim 1, wherein in the formula, a:b:c=4.8-7.2:6:16.8-25.

2.

4. 2. The composite oxide particles according to claim 1, wherein in the formula, a:b:c=9.6-14.4:6:24-36.

5. A method for producing oxysulfide particles, comprising a step of combining the composite oxide of the composite oxide particles according to any one of claims 1 to 4 with sulfur.

6. The method for producing oxysulfide particles according to claim 5 , wherein sulfur is combined with the composite oxide by solid phase synthesis.

7. The method for producing oxysulfide particles according to claim 6 , wherein sulfur is compounded with the composite oxide by solid phase synthesis using a flux.

8. The method for producing oxysulfide particles according to claim 7 , wherein an iodide is used as the flux.

Citation Information

Patent Citations

  • Photocatalyst, and method for producing hydrogen and oxygen using said photocatalyst

    JP2020138188A